Las fronteras del neoextractivismo en América Latina Conflictos socioambientales, giro ecoterritorial y nuevas dependencias - Svampa, Maristella (Afrontar las crisis desde América Latina, 2019)
This book analyzes the progress of neoextractivism in Latin America through four fundamental nuclei: the first proposes the categories of neoextractivism and Consensus of Commodities as privileged windows to read the current crisis; the second analyzes the phases of neoextractivism from 2003 to the present; the third addresses the social resistance and the new political grammars from the concept of the ecoterritorial turn, and highlights the advance of indigenous peoples and the growing role of women; and the fourth illustrates the expansion of the frontiers of extractivism: criminal territorialities, patriarchal violence and extreme energies.